Pengembangan Sistem Informasi Pengelolaan Keuangan Bagi Usaha Mikro Kecil dan Menengah (UMKM) - Ivan Faizal; Indra Nanda; Deny Ariestiandy; Tia Ernawati (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Accounting plays an important role in the progress of MSMEs. However, so far, there are still many MSMEs who do not understand the importance of accounting implemented in financial reports, even though this is very beneficial for the business development of MSME actors. The development of an Accounting Information System for MSMEs is considered feasible and important to do because the accounting information system will add value to the MSME actors. This study focuses on the development of a financial management information system for MSMEs which was built by applying the Extreme Programming (XP) method. This financial management information system for MSMEs has been successfully developed with features for managing account data, managing general journals, displaying ledgers and trial balances. The features in this system can help MSME actors in recording and managing finances. Based on black box testing, the resulting system is in accordance with user needs with a functionality test value of 100%.